چونویں پنجابی ناولاں وچ سامراجی تے جاگیرداری نظام دی نندیا: اک تحقیقی جھات: NEGATION OF IMPERIALISM AND FEUDAL SYSTEM IN SELECTED PUNJABI NOVELS: A RESEARCH STUDY (Al-Aasar, 2025)
Exploitation has been with human in every age and society. The powerful have always exploited the poor, the man has exploited the woman and sometimes the woman has exploited the man, the government has exploited its subjects, the officer has exploited its subordinates, the big has exploited the small, and perhaps to some extent it will continue to do so for the rest of the world.Even big Juries have exploited the oppressed class. Sometimes this exploitative class kills someone's right, steals someone's honor, snatches someone's right to live, sometimes humiliates and exploits the lower ones for their own honor and small happiness, because this class considers these poor people as their slave. However, as education and awareness is coming to the people, the grip of this exploitative class is decreasing. Like other literatures of the world, in Punjabi literature, the writers have rejected this imperialist and feudal system in every era.   Through this article, Scholar will present a research review on the negation of imperialism and feudalism in selected Punjabi novels.